Temporal regulation of dendritic spines through NrCAM-Semaphorin3F receptor signaling in developing cortical pyramidal neurons - Mohan, Vishwa; Sullivan, Chelsea S.; Guo, Jiami; Wade, Sarah D.; Majumder, Samarpan; Agarwal, Amit; Anton, Eva S.; Temple, Brenda S.; Maness, Patricia F. (Cerebral cortex, 2019)
Abstract. Neuron-glial related cell adhesion molecule NrCAM is a newly identified negative regulator of spine density that genetically interacts with Semaphori
Published: 03 February 2018
Gesehen am 14.06.2019